The Effect of Hydrogen Peroxide and Povidone-Iodine on the Shear Bond Strength of Orthodontic Brackets: An In Vitro Study - Ghobadi, Alireza; Golshah, Amin; Safaei, Mohsen (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Chlorhexidine, which is the gold-standard antimicrobial mouthwash, cannot effectively decrease the count of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which is the causative agent for coronavirus disease-2019 (COVID-19). Since SARS-CoV-2 is susceptible to oxidation, mouthwashes containing oxidizing agents such as hydrogen peroxide (H2O2) or Povidone-iodine (PVP-I) are recommended to decrease the viral count. AIM: This study aimed to assess the effects of H2O2 and PVP-I mouthwashes on the shear bond strength (SBS) of metal orthodontic brackets to the enamel. MATERIALS AND METHODS: This in vitro experimental study evaluated 45 freshly extracted maxillary premolars. The teeth were cleaned and randomized into three groups (n = 15) for rinsing with distilled water (control group), 1% PVP-I (betadine), and 1.5% H2O2 for 60 s. All teeth were etched with 37% phosphoric acid gel, and metal orthodontic brackets were bonded to the teeth using the Transbond XT bonding system. The teeth were mounted in auto-polymerized acrylic resin and incubated in water at 37°C for 72 h. The teeth were then thermocycled for 48 h, and their SBS was measured in a universal testing machine. The adhesive remnant index (ARI) score was also calculated. The groups were compared by ANOVA and Chi-square Monte Carlo test. RESULTS: No significant difference was noted among the three groups in SBS (p = 0.938) or the ARI score (p = 0.780). CONCLUSION: Use of H2O2 and PVP-I mouthwashes has no adverse effect on SBS or mode of failure of metal orthodontic brackets bonded to enamel.